WUJUD NYATA PENDIDIKAN KARAKTER DI SMP NEGERI 27 MAKASSAR - Andi Saadillah; Nurul Haeniah; Jumriah (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2021)
Character education aims to build character and character by instilling good character values ??in children from elementary school to higher education. The achievement expected by the school with the application of character education is that students are expected to have good character, polite behavior and behavior, and when outside the school environment students still have good character. To realize this, it can be seen from the school regulations that have been prepared in accordance with the school's vision and mission, so that the implementation of character education goes well, then the teacher as a means to provide good habits and motivate children so that children have good and strong character. Keywords: Real, Education, Character